An Exploratory of Thai Herbs Supply Chain Connectivity: A Case Study - Variskhanov, Anvar; Sirisawat, Pornwasin; Hasachoo, Narat; Kaewket, Thunwa; Suwanwong Rodbundith, Tipavinee (International Journal of Multidisciplinary in Management and Tourism, 2022)
The worldwide demand for herbs is increasing yearly, especially in the treatment and beauty industry. The northern part of Thailand is one area that grows herbs and supports domestic and international markets. Even though growing herbs in the Northern area generate a high value in the Thailand herbs market, the stakeholders in the supply chain system of the herbs business are still faced with some barriers which affect the performance of the company, the quality of the products, and marketing. Therefore, this study aims to investigate the current situation of Thai herbs' supply chain management system and also find the essential barriers and opportunities for Thai herbs' supply chain management. This study focused on the three potential herbs, which are Limonella (Zanthoxylum Limonella), Turmeric (Curcuma longa Linn), and Kariyat (Andrographis paniculate). The unstructured interview was used to collect the data from the stakeholders in the supply chain system. The finding of this study found that there are some barriers, such as market distance barriers, marketing barriers, and lack of laboratory tests. Different opportunities arise for Thai herbs' supply chain management, which includes resourceful location, adequate labor force, government promotion, and international market demand. The results of this study can be the guideline for further research of researchers and other related industries.